Structural and magnetic properties of type-m barium ferrite– thermoplastic natural rubber nanocomposites - Nurhidayaty Mokhtar,; Mustaffa Hj. Abdullah,; Sahrim Hj. Ahmad, (Universiti Kebangsaan Malaysia, 2012)
Structural and magnetic properties of type-M barium ferrite (BaFe12O19) nanoparticles (~ 20 nm) embedded in non-magnetic thermoplastic natural rubber (TPNR) matrices were investigated. The TPNR matrices were prepared from high density polyethylene (HDPE) and natural rubber (NR) in the weight ratios of 80:20 and 60:40, respectively, with 10 wt% of NR in the form of liquid natural rubber (LNR) which act as a compatibiliser. BaFe12O19 – filled nanocomposites with 2 – 12 wt% BaFe12O19 ferrite were prepared using a melt- blending technique. Magnetic hysteresis was measured using a vibrating sample magnetometer (VSM) in a maximum field of 10 kOe at room temperature (25oC). The saturation magnetisation (MS), remanence (MR) and coercivity (Hc) were derived from the hysteresis loops. The results show that the structural and magnetic properties of nanocomposites depend on both the ferrite content and the composition of the natural rubber or plastic in the nanocomposites. All the nanocomposites exhibit an exchange bias-like phenomenon resulting from the exchange coupling of spins at the interface between the core ferrimagnetic region and the disordered surface region of the nanoparticles.